The global biopolitics of the IUD : how science constructs contraceptive users and women's bodies - Takeshita, Chikako, 1963- (Inside technology., 2012)
This is a biography of a multifaceted technological object, the IUD. The book illuminates how political contexts shaped contraceptive development, marketing, use, and users.